OPTIMIZATION OF PUMPING AND WATER FILTRATION FOR SUBTERRANEAN RIVER OF GOA TUK SARINING KEMBANG IN THE INTEREST OF WATER FULFILLMENT IN GEBANG HAMLET AND ITS SURROUNDING - Heru Sigit Purwanto; Bambang Sugiarto; Dedi Fatchurohman (Techno LPPM, 2020)
Water is the primary needs for the livelihood of people in Gebang hamlet, Girisuko village, Gunung Kidul Regency, Special Region of Yogyakarta. Gebang is a hamlet in Panggang district, Gunug Kidul Regency, of which water supply is insufficient to meet the needs. There are 170 households with an average of 4 lives each, thus about approximately 680 people don’t have sufficient water supply. Water supply to the hamlet is constrained by the pumping ability.The neighborhood rely on overflowing raw water in high rainfall season that is channelled through pipe to the certain water tank prepared as reserves for dry season and few of them had used water from a cave. However, the pump is now broken so in a long dry season they need to buy water using tank truck. Based on the observation, this research planned to design water pump arrangement with high capacity so water can easily be channeled to the water tank and distributed to people in the neighborhood.The material absorbed in karst medium is related to each other, between organic (coliform parameter) and anorganic material (TDS parameter). The water puryfying process was conducted in laboratory and another process engaging gravity sand filter was chosen using zeolith with thickness of 40-50 cm that is able to decrease TDS from 232 – 268 ppm up to 180 ppm.